2018
DOI: 10.1002/pssr.201800488
|View full text |Cite
|
Sign up to set email alerts
|

Effective Use of UV‐Ozone Oxide in Silicon Solar Cell Applications

Abstract: It is long recognized that high‐quality surface cleaning is critical for an increased performance of solar cells and semiconductor devices. In this contribution, the effectiveness of UV‐ozone cleaning by comparing it against the industry standard RCAand UV‐assisted deionized water (DI‐O3) techniques has been demonstrated. UV‐ozone cleaning results in an effective surface passivation quality that is comparable to both RCAand DI‐O3 cleans, realizing a recombination current density (J0) of 7 fA cm−2 as compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Using the application example of organic semiconductor components, the necessary hole-injection layer (HIL) for example, poly(3,4-ethylene-dioxythiophene): poly(styrenesulfonate) (PEDOT: PSS) is typically prepared from a water-based solution [39][40][41]. Therefore, the surface must be clean and primed hydrophilic to allow subsequent coating processes.…”
Section: Introductionmentioning
confidence: 99%
“…Using the application example of organic semiconductor components, the necessary hole-injection layer (HIL) for example, poly(3,4-ethylene-dioxythiophene): poly(styrenesulfonate) (PEDOT: PSS) is typically prepared from a water-based solution [39][40][41]. Therefore, the surface must be clean and primed hydrophilic to allow subsequent coating processes.…”
Section: Introductionmentioning
confidence: 99%
“…In this quest, the ozone-based oxidation technique is exquisitely implemented in processing of c-Si solar cells. [27][28][29][30] Previous studies [31][32][33] showed the potential of ozone-dissolved deionized water (DI-O 3 ) oxide for surface passivation and cleaning in c-Si solar cells. However, there is lack of work on pinholes investigation in DI-O 3 oxide layers.…”
Section: Introductionmentioning
confidence: 99%